Inflammatory markers in conventional vs. active robot-assisted total knee arthroplasty and other variables - Abhinandan S. Punit; Karthik Sangani; B. N. Prashanth; Ihjas Ismail; S. Satish Kumar (BMC Musculoskeletal Disorders)
Abstract Background Conventional Total Knee Arthroplasty (CTKA) has long been the standard for arthroplasty. Recent technological advancements have introduced Robot-Assisted Total Knee Arthroplasty (RATKA) and its more automated versions, such as active RATKA offering enhanced precision, accuracy, and potentially superior outcomes. Their role in inflammatory markers has been sparsely explored. Inflammatory response has a direct effect on functional recovery following joint replacement. Our study aimed to understand the natural progression of these inflammatory markers post-surgery. It compared the inflammatory response of CTKA and active RATKA to identify their differences. It also evaluated the role of comorbidities, gender, tourniquet usage, and unilateral or bilateral surgery on inflammatory markers. Methods CRP, IL6, ESR, and TLC were measured preoperatively, on postoperative day 2 (POD2), POD14, and POD30 in 192 consecutive cases of TKA. Results CRP increased from 6.59 mg/ml(SD 4.92) preop to 190.57 mg/ml(SD 77.62) on POD2, then decreased to 53.55 mg/ml(SD 42.3) on POD14 and 16.72 mg/ml(SD 14.04) by POD30(p-0.001). ESR rose from 18.81 mm/hr(SD 7.17) preop to 62.78 mm/hr(SD 34.41) on POD2, with a decrease to 57.05 mm/hr(SD 26.63) on POD14 and 27.18 mm/hr(SD 22.42) by POD30(p-0.001). IL6 was markedly elevated at 163.60pg/ml(SD 51.05) on POD2 compared to 6.55pg/ml(SD 2.58) preop(p-0.001). The RATKA group had lower CRP, ESR, and TLC levels than CTKA (p < 0.05). Diabetes Mellitus was associated with increased inflammation (p < 0.05). Conclusion RATKA cases showed a lower inflammatory response in several markers and slightly better pain scores compared to the conventional approach. Factors such as tourniquet usage and patient gender did not significantly impact inflammatory markers. Among the comorbidities, Diabetes Mellitus increased inflammation. In the majority of the normal patients, the inflammatory markers did not return to the normal reference even 1 month post-surgery. This physiological variation should be considered when assessing for potential prosthetic joint infections.